Odpowiedzi

  • Użytkownik Zadane
2009-12-11T21:10:37+01:00
A)
5=3x-y
5x-2y=7

3x-y=5 |*5
5x-2y=7 |*(-3)

15x-5y=25
-15x+6y=-21

6y-5y=(-21)+25
y= 4

5=3x-y y=4
5=3x-4
3x=-4-5
3x=9 |/3
x=3

b)
x-3y=5
y+3x=-5 |*3

x-3y=5
3y+9x=-15

9x+x=-15+5
10x=-10 |/10
x=1

x-3y=5 x=1
1-3y=5
-3y=5-1
-3y=4 |/-3
y= -1 ⅓
5 3 5
2009-12-11T21:25:09+01:00
1)
3x-y=5 /*-2
5x-2y=7

-6x+2y=-10
5x-2y=7
-x=-3/: (-)
x=3
teraz podstawiamy wybrane wyrazenie z układu
3x-y=5
3*3-y=5
9-y=5
-y=5-9
-y= -4/:(-)
y=4
x=3


2)
x-3y=5
y+3x=-5

-3y+x=5
y+3x=-5 /*3

-3y+x=5
3y+9x=-15
10x=10
x =1
teraz podstawiamy
x-3y=5
1-3y=3
-3y=3-1
-3y=2/:(-3)
y=minus dwie trzecie
x=1



udało mi sie 2 zrobić